Inhalation Administration of Agarwood Incense Rescues Scopolamine-Induced Learning and Memory Impairment in Mice - Han, Muxuan; Zhang, Hao; Hu, Minghui; Sun, Wei; Li, Zifa; Cao, Guimao; Geng, Xiwen; Wei, Sheng (Frontiers in Pharmacology, 2021)
Background: Agarwood, a type of herbal medicine widely used in Asian countries, is noted in traditional medicine for its intelligence-enhancing effects. Agarwood incense is traditionally administered by oral and nasal inhalation. To verify whether agarwood incense can exert its intelligence-enhancing effects in this way to rescue learning and memory impairment, typical clinical manifestations of dementia, we conducted a set of behavioral tests related to learning and memory. Methods: C57BL/6 mice were divided into six groups. In addition to the control and model groups, we added a donepezil treatment group to evaluate the effect of three different agarwood administration doses. After a week of administration, scopolamine was injected 30 min before each behavioral test to create a learning and memory impairment model. A series of behavioral tests (the Morris water maze test [MWM], the novel object recognition test [NOR], and the step-down test [SDT]) were used to assess their learning ability, as well as their spatial and recognition memory. Results: After scopolamine injection, the model group showed significant learning and memory impairment (i.e., longer latencies, lower crossing times, and lesser distance travelled in the target quadrant in MWM; a lower recognition index in NOR; and longer latencies and higher error times in SDT). The other four treatment groups all showed improvements in these indicators, and the overall therapeutic effect of agarwood was superior. Conclusion: The inhalation administration of agarwood can significantly improve the learning and memory impairment caused by scopolamine in mice, and the therapeutic effect varied between doses.